2021
DOI: 10.37616/2212-5043.1243
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Left Ventricular (LV) Thrombus after ST-Elevation Myocardial Infarction (STEMI) in the Holy Capital of Saudi Arabia

Abstract: Background Patients with acute myocardial infarction (AMI) especially those with large MI (myocardial infarction) as identified by ST elevation in multiple contiguous ECG leads or anterior MI, may suffer significant myocardial damage leading to impaired wall motion and contractility which may lead to the formation of left ventricular thrombus (LVT) in the patient. This study was aimed to establish the incidence of LV thrombus and determine the predictors associated with the formation of LV thrombu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Previous studies showed that LVT formation was significantly associated with lower EF. [ 13 , 24 , 25 ] However, in this investigation, HFmrEF and HFpEF were found to be independent risk factors for in-hospital ST, which indicated that the thrombus can easily be detached. In patients with HFpEF or HFmrEF, the compensatory motion of the ventricular wall in the non-infarct area is enhanced, and the contradictory motion is more prominent, which may increase the likelihood for thrombus detachment.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Previous studies showed that LVT formation was significantly associated with lower EF. [ 13 , 24 , 25 ] However, in this investigation, HFmrEF and HFpEF were found to be independent risk factors for in-hospital ST, which indicated that the thrombus can easily be detached. In patients with HFpEF or HFmrEF, the compensatory motion of the ventricular wall in the non-infarct area is enhanced, and the contradictory motion is more prominent, which may increase the likelihood for thrombus detachment.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have evaluated the predictors for thrombus genesis, [7][8][9] but most of the published data were obtained from case reports. [10][11][12][13][14][15][16] For example, Paolo Rubartelli et al reported that hypercoagulable state and myocardial dysfunction contributed to LVT formation in COVID-19 patients. Additionally, a recent meta-analysis showed anticoagulation and triple therapy were independent predictors of lower rates of embolic events in LVT.…”
Section: Introductionmentioning
confidence: 99%
“…There was highly significant difference between the groups with and without LVT as regard anterior STEMI, 94% of patients with LVT have anterior STEMI. Also, the study by Niazi et al, [14] reported that in the LVT there were 86% have anterior STEMI and in the Without LVT group 52% had anterior STEMI with high significant difference.…”
Section: Discussionmentioning
confidence: 92%
“…The underlying endomyocardial pathological changes and low regional intracardiac blood flow velocity caused by MI are the most important mechanisms of thrombus formation ( 13 , 14 ). In most instances, a hypercoagulable state may also contribute to some extent ( 5 , 6 ).…”
Section: Discussionmentioning
confidence: 99%